Performance Test Membrane Contactor for CO2 Desorption from DEA - Yeni Rahmawati; Salasa Ariq Sungkono; Zulfahmi Hawali; Fadlilatul Taufany; Susianto; Siti Nurkhamidah; Ali Altway (IPTEK The Journal of Engineering, 2023)
Membrane-based desorption of carbon dioxide (CO2) using a membrane contactor is considered a novel process for separating CO2 from solvents. It can be carried out using temperature regeneration, sweep gas, and vacuum method. In this work, the vacuum regeneration method is applied in the CO2 desorption process from 30% wt of diethanolamine (DEA) solution. This study investigates the effect of operating parameters such as liquid flowrate, vacuum pressure, and CO2 loading on the mass transfer rate and desorption efficiency of CO2. The highest mass transfer rate of 2.2013 × 10-7 mol/m2s is achieved at a liquid flowrate of 500 mL/min, CO2 loading of 0.27 mol CO2/mol DEA, and vacuum pressure of 50 cmHg while the maximum desorption efficiency of 71.45% is achieved at lower liquid flowrate of 100 mL/min, CO2 loading of 0.27 mol CO2/mol DEA, and vacuum pressure of 50 cmHg. The result demonstrates that membrane contactor is a promising method for the CO2 desorption process which requires further investigation.